Meningkatkan Manajemen Sumber Daya Manusia dan Personal Branding Santri melalui Metode STIFIn di Pondok Tahfiz Putri Bani Ibrahim Palangka Raya - Andani, Normery (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The application of the STIFIn method at Pondok Tahfiz Putri Bani Ibrahim in Palangka Raya seeks to improve Human Resource Management (HRM) and enhance the personal branding of santri. This community service activity was driven by the need to provide a personalized learning approach that aligns with each santri’s natural tendencies and potential. The goal of the program is to optimize their memorization skills, character building, and self-confidence to prepare them as well-rounded individuals in society. The activity employed methods such as personality identification using the STIFIn framework, tailored training sessions, and mentoring programs focusing on HRM strategies and personal branding. The results showed that this approach improved the effectiveness of learning processes, increased santri’s self-awareness, and strengthened their personal branding. This initiative not only contributed to the institution’s mission of creating Quranic generations but also equipped the santri with essential life skills for broader societal engagement.